THE IMPACT OF ORGANIZATIONAL STRUCTURE AND ADMINISTRATIVE POLICES OF HOSPITALS ON DELIVERING QUALITY OF SERVICE FOR PATIENTS SATISFACTION - Amoah-Binfoh, Kenneth; Lakhawat, Pradhyuman Sing; Agyapong, Rita (Homes Journal: Hospital Management Studies Journal, 2021)
Background: A well-organized hospital will determine the kind of service it will render to its patients. This diverse mix of objectives determine the nature of the hospital, its organizational hierarchy, the scope and volume of activities, the number and size of departments, staffing patterns, etc. Objective: The study seeks to examine the health workers and in-patient’s relationship building and to identify the importance of organizational structure in delivering quality services to in-patients. Method: The researchers considered a total of 35 management, and 70 in-patients together in all 105 as the sample size. These consisting of both males and females working in the various functional areas, and operations in the Hospital. This sample size was chosen because it formed a fair representation of the population. Simple random sampling was the sampling technique used for the study. Result: This output also shows that Patients satisfaction have a high positive relationship with Environment & physical ambience, Payment process & Discharge process ,Information flow to family about patient condition & treatment, Janitorial (daily cleaning), and Doctors information about treatment & concerns (administrative polices). Conclusion: It was also recommended that; Management should reduce the number of health workers working under a superior and should also reduce the number of superiors’ management reports to. It was further recommended that, management should, improvement the clarity of communication and information giving to patients’ relatives on patients’ condition and Management should also paste the vision and mission statement of the hospital on walls and vantage points for reminder.